1983
DOI: 10.1203/00006450-198302000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The in Vitro and in Vivo Photoreactivity of Bilirubin: I. Laser-Defined Wavelength Dependence

Abstract: SummaryMonochromatic light was provided by a continuous wave Argon ion laser. We chose to study the in vitro effects of light at 457.9, 465.8, 476.5, 488.0, 501.7, and 514.5 nm as representative of a reasonably evenly spaced samplig across the blue-green spectrum. The in vivo experiments were conducted at 457.9, 476.5, 488.0, and 514.5 nm.In vitro light at 488.0 nm appeared to be more effective than the others studied.After 24 h of irradiance, the in vivo decline in serum bilirubin concentration produced by li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
1

Year Published

1984
1984
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
(35 reference statements)
2
4
1
Order By: Relevance
“…Because of the experimental design, the physiological relevance of that study is questionable: photoisomerization reactions were neglected, photoreactions were allowed to go to high conversion and performed on unstirred solutions in cells of long photochemical pathlength, and samples had higher optical thicknesses at 457.9 and 488.0 nm than at longer wavelengths. The results disagreed with those of several other more detailed studies (Gutcher et al, 1983;Lightner et al, 1980;Raethel, 1975), probably because of a failure to recognize the effects of optical thickness differences. Nevertheless, clinical trials (which did not include a control group of unirradiated infants) have indicated that green lights do have a phototherapeutic effect (Sbrana et al, 1987), though they are not more effective than blue lights (Foschi et al, 1986;Ayyash et al, 1987a, b).…”
Section: Clinical Implications; Green Light Phototherapycontrasting
confidence: 89%
See 1 more Smart Citation
“…Because of the experimental design, the physiological relevance of that study is questionable: photoisomerization reactions were neglected, photoreactions were allowed to go to high conversion and performed on unstirred solutions in cells of long photochemical pathlength, and samples had higher optical thicknesses at 457.9 and 488.0 nm than at longer wavelengths. The results disagreed with those of several other more detailed studies (Gutcher et al, 1983;Lightner et al, 1980;Raethel, 1975), probably because of a failure to recognize the effects of optical thickness differences. Nevertheless, clinical trials (which did not include a control group of unirradiated infants) have indicated that green lights do have a phototherapeutic effect (Sbrana et al, 1987), though they are not more effective than blue lights (Foschi et al, 1986;Ayyash et al, 1987a, b).…”
Section: Clinical Implications; Green Light Phototherapycontrasting
confidence: 89%
“…Our data indicate that blue or blue-green light in the 480-510 nm region is likely to be the best for phototherapy, as suggested by experiments in jaundiced rats (Gutcher et al, 1983) and originally recommended when phototherapy was introduced (Broughton et al, 1965;Cremer et al, 1958). Although lights emitting maximally at the BR absorption maximum (Tan, 1982) are probably not the most effective, there seems to be no compelling scientific reason at present for using narrow-band green lights with peak emission near 525 nm in preference to lights that have better overlap with the long wavelength side of the BR absorption band.…”
Section: Clinical Implications; Green Light Phototherapysupporting
confidence: 72%
“…Numerous studies have been done on lysosomal glycosidases but few consistent findings have been reported. Among the most reproducible of the findings on glycosidases is the significant elevation of a-D-glucosidase activity in CF tissues (2)(3)(4)(5)(6)(7). In a previous study we confirmed the fact that neutral a-D-glucosidase activity is significantly elevated in CF sera (2).…”
Section: Discussionsupporting
confidence: 78%
“…From the clinical point of view the most effective spectral region of BR degradation in the organism is still considered that matching the visible absorption spectrum maximum of BR in vitro (-450 nm). However, recent investigation of BR photodegradation in vitro and in vivo made with monochromatic optical sources (lasers) shows that other spectral regions at longer wavelengths may be more suitable for phototherapy (5,17). The use of lasers for the analysis of the photophysical and photochemical properties of BR and of its photoproducts has been found to be particularly suitable due to their monochromaticity and frequency tunability, which make it possible to show up small differences in the physical and chemical behavior of PBRs.…”
mentioning
confidence: 99%
“…15 This cobinding results in a shift in the absorption maximum of bilirubin to longer wavelengths. 17 In addition, it has been noted that the absorption spectrum of bilirubin may be modified when bound to skin constituents 18 and by the filtering action of skin layers. 16 The apparent efficacy of the green fluorescent lamps used in some of these clinical studies can be attributed to the not unimportant contribution of blue light present in these lamps.…”
Section: Discussionmentioning
confidence: 99%